A Synergistic Framework for Curriculum Development, Construction, and Evaluation in Media Education Driven by Industry Needs - Chen, Yang (Education Insights, 2025)
This review paper explores a comprehensive and synergistic framework for curriculum development, construction, and evaluation within the field of media education, placing a primary emphasis on strict alignment with contemporary industry needs. As the digital landscape undergoes unprecedented transformations driven by emerging technologies, the introduction outlines the critical importance of bridging traditional academic curricula with rapidly evolving professional demands. A detailed historical overview traces the pedagogical evolution of media education, highlighting its historical responsiveness to major technological breakthroughs and paradigm shifts in professional practice. Furthermore, the core themes of this review systematically analyze contemporary curriculum design methodologies, innovative construction strategies, and robust evaluation metrics, with a specific focus on their seamless integration into a unified, cohesive educational framework. Comparative analyses critically highlight persistent pedagogical challenges, such as effectively balancing foundational theoretical knowledge with highly specialized practical skills, and adapting institutional structures to accommodate rapid industry changes. To address these ongoing challenges, future perspectives propose the implementation of predictive modeling and highly adaptive learning frameworks designed to ensure that academic curricula remain continuously relevant and forward-looking. Ultimately, the conclusion synthesizes these critical findings and strongly emphasizes the indispensable need for sustained, dynamic collaboration between academic institutions and industry stakeholders to foster the next generation of media professionals.